Poetry in the age of the internet - Kiiskinen, Jyrki; Santanen, Eino; Rimminen, Mikko; Vähänen, Juhana; Sinivaara, Olli; Hackston, David (Books from Finland, 2006)
s. 192 We have to / Mikko Rimminen ; s. 194 My neighbour estimated how much the water pipe was hissing / Eino Santanen ; s. 196 I walked the long tongue from end to end / Juhana Vähänen ; s. 198 A windbell-shaped light / Olli Sinivaara
Keywords: lyriikka : Suomi : 2006; runot : käännökset; lyrik : Finland : 2006; poems : translations